2014
DOI: 10.1055/s-0034-1383062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraperitoneal Thymoquinone on Chronic Neuropathic Pain in Rats

Abstract: In this study, we evaluated the protective effects of thymoquinone, the major constituent of Nigella sativa seeds on the neuropathic pain of rats with chronic constrictive injury of the sciatic nerve. Rats received repeated administration of thymoquinone (1.25, 2.5, and 5 mg/kg, i. p.) once a day for 14 days, beginning immediately after the nerve injury. Mechanical allodynia, cold allodynia, and thermal hyperalgesia were assessed with the von Frey filament, acetone drop, or radiant heat stimulus, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Cell culture studies and animal models have indicated several therapeutic potentials, such as anti-cancer [5, 79], antimicrobial [10, 11], analgesic [12, 13], antipyretic [14], contraceptive and anti-fertility, anti-oxytocic [3], anti-tussive [15], anti-inflammatory [12, 16], and anti-oxidant [1719] potentials, for black seed and its active component TQ. NS or TQ anticancer activity has been demonstrated for blood, breast, colon, pancreatic, liver, lung, fibrosarcoma, prostate, and cervix cancer cell lines and in animal models of lung, kidney, skin, colon, and breast cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture studies and animal models have indicated several therapeutic potentials, such as anti-cancer [5, 79], antimicrobial [10, 11], analgesic [12, 13], antipyretic [14], contraceptive and anti-fertility, anti-oxytocic [3], anti-tussive [15], anti-inflammatory [12, 16], and anti-oxidant [1719] potentials, for black seed and its active component TQ. NS or TQ anticancer activity has been demonstrated for blood, breast, colon, pancreatic, liver, lung, fibrosarcoma, prostate, and cervix cancer cell lines and in animal models of lung, kidney, skin, colon, and breast cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] Effects of TQ on the peripheral nervous system were reported in 3 studies. [10,11] The first of these was performed in an experimental streptozotocin-induced diabetic neuropathy model. The authors reported that TQ improved ultrastructural features of axons remarkably.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In the second study, Amin et al used a rat model of chronic neuropathy and concluded that TQ plays an anti-nociceptive role, possibly by exerting antioxidant effects and inhibiting microglial activity. [11] However, no published studies have assessed the acute effects of TQ in a peripheral nerve model. Current histological and stereological results suggest that TQ has no therapeutic effect on acute nerve injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] However,T Qc an be obtained in large quantities through the oxidation of carvacrol and thymol( Scheme 1), which are abundantly available in oregano essential oils. [1][2][3][4][5][6][7] However,T Qc an be obtained in large quantities through the oxidation of carvacrol and thymol( Scheme 1), which are abundantly available in oregano essential oils.…”
Section: Introductionmentioning
confidence: 99%